Why agriculture remains a viable means of poverty reduction in sub-Saharan Africa: The case of Ethiopia - Dorosh, Paul A.; Mellor, John W. (Wiley, 2013)
Although there is much empirical evidence of the importance of agricultureled economic growth, there is a renewed emphasis in development circles on the industrial sector as the main driver of growth, even for the low‐income countries of sub‐Saharan Africa. This article applies a simplified model of agricultural growth linkages to illustrate the importance of agricultural growth for increasing employment and accelerating poverty reduction in Ethiopia. Achieving rapid agricultural growth, however, will require the engagement of small commercial farmers, large enough to adopt new technologies and produce significant marketed surpluses, but small and numerous enough to have spending patterns that drive a large, vibrant rural non‐farm sector.